Changes in Pedagogical University Students' Creativity while being Taught According to a Special Program - Grakauskaitė-Karkockienė, Daiva (Acta Paedagogica Vilnensia, 2006)
The study tried to evaluate the special program effectiveness on students' fluency, flexibility and originality and how the program changed the students' subjective evaluations of one's one creativity. In this study it was analysed the results of 2 tests: Torrance test (TICT, form A) for measuring creativity and Dembo-Rubinstein method for evaluating creativity, originality, and the ability to create ideas. The results have shown that it's possible to create the program for developing students' creativity. The program we have proposed is effective. The positive effect was observed immediately after the completion of the program. The comparative analysis between experimental and control groups of all cognitive parameters of creativity (fluency, flexibility and originality) evaluated by Torrance test (TICT, verbal A form) as well as subjective evaluations of one's own creativity by Dembo-Rubinstein test has showed the positive influence to students' creativity. It was observed that while students from the experimental group perceived themselves as mare creative after completing the program, the students from the control group perceived themselves as the same or even less creative level the second time they were requested to classify themselves in a scale of creativity, originality, ability to create ideas and curiosity. Most students who participated in the program emphasized the importance and interest to this program during the learning process of psychology discipline. The program was considered very useful by students who pointed to the fact that the program contributed to the development of their own creative abilities and changed their view to their own abilities to be creative, original, ability to create new ideas and awoke their curiosity to know more about creativity. The program could be adopted while being taught different disciplines in universities and schools seeking to develop students' creativity during the learning process.
Keywords: Creativity; Divergent thinking; Fluency; Flexibility; Original ity; Enhancement of Creativity; Programs in Creativity